Transformasi Digital dalam Etnomusikologi: Peluang dan Tantangan bagi Riset di Nusantara - Ariel Januar Chrisnahanungkara; Agung Supriono (Mahāsarā, 2026)
Digital transformation in the last two decades has reconfigured the production, distribution, documentation, and research of traditional music across the globe, including in archipelagic regions like Indonesia. This article aims to conceptually analyze how the digital shift transforms the paradigm of ethnomusicology and its implications for research in the Indonesian archipelago (Nusantara). This study employs a conceptual approach through a critical literature review of platform mediation studies, online ethnography, computational ethnomusicology, artificial intelligence (AI), and archipelagic studies. The analysis indicates that digitalization expands archive access, increases visibility for previously marginalized regions, and enables cross-island and transnational collaborations. However, this transformation also presents serious challenges such as the commodification of identity via algorithms, computational bias against non-Western musical systems, the reduction of ritual context in digital clips, and ethical issues regarding representation and data ownership. This article proposes four dimensions of digital transformation in archipelagic ethnomusicology: platform mediation, computation and AI, digital pedagogy, and methodological adaptation. This framework emphasizes the importance of a hybrid approach between online and offline work, cultural sensitivity in technological design, and decolonial reflection on global digital infrastructure. The contribution of this article lies in the integration of digital transformation theory with the concept of "islandness" as a conceptual foundation for the development of Indonesian ethnomusicology in the digital age.